PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS ( RETURN ON ASSET ) PADA PT. QUIKSILVER INDONESIA - Ida Bagus Swaputra; Tjok Istri Sri Harwati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Profitability as the company's ability to obtain profit in relation to sales, total assets and equity are often used to measure the efficiency of the use of capital in a company by comparing the income with capital employed in operations. Negative profitability due to the company's profit or loss is negative, it indicates the ability of the invested capital as a whole has not been able to generate profits. and vice versa, positive profitability due to the company's profit is positive, it means investing in assets has been able to generate profits or gains. PT.Quiksilver Indonesia is a company that sells surfing products, accessories, shoes, bags and etc. In this study, using a variable Receivable Turnover, Working capital turnover and Return on Assets (ROA). The purpose of this study was to investigate the influence receivables turnover and turnover of working capital either partially or simultaneously to ROA in PT.Quiksilver Indonesia. Data used in this research is quantitative data with the primary data source. Methods of data collection was done by using the documentation, while the analysis technique used is quantitative analysis, the classical assumption test, multiple linear regression and hypothesis testing. Results from this study indicate that in partial receivables turnover significant positive effect on ROA, thus the hypothesis is accepted. While variable working capital turnover significant negative effect on ROA, thus the hypothesis is rejected. Simultaneously turnover of receivables and working capital turnover significantly influence the ROA, the hypothesis in this study received. The advice can be given that the company should further improve working capital turnover to evaluate and manage well so that the amount of working capital as required.